Obstacles of the international criminal court - Dr. Shvan Ahmed Abduqader Alaziz (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The International Criminal Court was created under the pressure and determination of the international community. However, after the Rome Statute entered into force, the Court faced a series of crises of loss of confidence and legitimacy. These crises reflected both: The Statue itself contains obstacles to the Court's exercise of its jurisdiction, and that the conduct of Statues in various areas, especially with the ICC, constitutes procedural obstacles which we have addressed in the midst of this research.